Profitable third-party punishment destabilizes cooperation - Raihan Alam; Tage S. Rai (Proceedings of the National Academy of Sciences, 2025)
Third-party punishment is theorized by some scholars to be essential to the evolution of large-scale cooperation, but empirically, it often fails to bring about its desired effects. Here, we suggest that third-party punishment destabilizes cooperation when third parties have profit motives to punish. Across nine economic games and judgment experiments (including four preregistered studies), we find that when third-party punishment is profitable, rates of cooperation decrease immediately and remain lower even when punishment outcomes are optimized to support cooperative behavior. Profitable third-party punishment causes targets of punishment to anticipate antisocial punishment and perceive social norms in terms of self-interest, suggesting that the introduction of payment degrades the communicative signals that punishment is meant to convey about punishers’ intentions and social norms. Critically, participants who would benefit from increased cooperation inadvertently reduce their own monetary compensation by opting in to experimental conditions that pay punishers, suggesting that they intuitively fail to consider the signaling consequences of profit motives to punish. Implications for systems of punishment and cooperation in real-world contexts are discussed.